Language Familiarity and Proficiency Leads to Differential Cortical Processing During Translation Between Distantly Related Languages - Shinozuka, Katsumasa; Niioka, Kiyomitsu; Tokuda, Tatsuya; Kyutoku, Yasushi; Okuno, Koki; Takahashi, Tomoki; Dan, Ippeita (Frontiers in Human Neuroscience, 2021)
In the midst of globalization, English is regarded as an international language, or Lingua Franca. Despite its increasing demand in international communication, handling it as a second language (L2) remains difficult for speakers of other languages, especially to the speakers of languages distantly related to English such as Japanese. To understand the neural basis for handling a distantly related L2, we focused on translation, which plays an important role for L1 speakers handling L2. There is a relatively high amount of previous research revealing brain activation patterns during translations between L1 and English as the L2. These studies, which focused on language translation with close or moderate linguistic distance (LD), have suggested that Broca’s area (BA 44/45) and the dorsolateral prefrontal cortex (DLPFC; BA 46) may play an important role in translation. However, the neural mechanism of language translation between Japanese and English with a large LD has not been clarified. Thus, we used functional near infrared spectroscopy (fNIRS) to investigate the brain activation patterns during word translation between Japanese and English. We also assessed the effects of translation direction and word familiarity. All participants’ first language was Japanese and they were learning English. Their English proficiency was advanced or elementary. We selected English and Japanese words as stimuli based on their familiarity to Japanese people. Our results showed that the brain activation patterns during word translation largely differed depending on their English proficiency. The advanced group elicited greater activation on the left prefrontal cortex around Broca’s area while translating words with low familiarity, but no activation was observed while translating words with high familiarity. On the other hand, the elementary group evoked greater activation on the left temporal area including the superior temporal gyrus (STG) irrespective of the word familiarity. These results suggest that different cognitive processes could be involved in word translation corresponding to English proficiency in Japanese learners of English. These differences in the brain activation patterns between the advanced and elementary groups may reflect a difference in the cognitive loads depending on the levels of automatization in one’s language processing.